Twelfth Meeting of the National Developmental Council Summary Records, New Delhi April 3 & 4, 1959 - Planning Commission (Planning Commission, 1959)
The production of foodgrains in the current season 1958-59, is expected to touch the level of about 70 million tons, thereby not only showing a recovery from the low output of 62 million tons in 1957-58 and also exceeding the output of 68 7 million tons achieved in 1956-57. The main increase has been in the case of rice, the production of which is estimated at 29 7 million tons as against the output of 28'3 million tons in 1956-57. The production of other kharif cereals is also expected to be better than in the previous year. The reports so far received about rabi crops are encouraging; there has been an increase in acreage under rabi cereals and there is every possibility of having a very good rabi crop too.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Participant; Agenda; Agenda Papers; Twelfth Meeting of the National Development Council; Agricultural Production; Resources; Organisational Aspects; The Ultimate Pattern; The I Interim Scheme; Cooperative Policy